Challenges in delivering therapeutic peptides and proteins: A silk-based solution - Wu, Junqi; Sahoo, Jugal Kishore; Li, Yamin; Xu, Qiaobing; Kaplan, David L. (Journal of controlled release, 2022)
Peptide- and protein-based therapeutics have drawn significant attention over the past few decades for the treatment of infectious diseases, genetic disorders, oncology, and many other clinical needs. Yet, protecting peptide- and protein-based drugs from degradation and denaturation during processing, storage and delivery remain significant challenges. In this review, we introduce the properties of peptide- and protein-based drugs and the challenges associated with their stability and delivery. Then, we discuss delivery strategies using synthetic polymers and their advantages and limitations. This is followed by a focus on silk protein-based materials for peptide/protein drug processing, storage, and delivery, as a path to overcome stability and delivery challenges with current systems. [Display omitted] •The challenges of delivering peptide and protein-based drugs are discussed•The advantages and limitations of synthetic polymer delivery system is introduced for protein and peptide-based drugs•Silk based delivery system is highlighted for deliverying and stabilizing protein and peptide-based drugs